Synthesis Of Carbon Nanotubes From Natural Gas Using Horizontally Continuous Rotary Reactor System - Zubir, Mohamad Syazwan Ahmad (2013)

(untitled)
The present research focuses on the synthesis of carbon nanotubes (CNT) from natural gas (NG) using continuous rotary reactor system. The catalyst of Co- Mo/MgO was used during the synthesis process. Three operating parameters were studied namely the reaction temperature, ratio of natural gas to nitrogen (NG:N2) and the reaction time. CNT produce were characterized using transmission electron microscope (TEM) and thermogravimetric analysis (TGA). The result shows that the decomposition of NG at 700°C, 800°C and 900°C not only produced the desired CNT but also produced carbon nanofibers (CNF). CNT produced had much smaller outer diameter (12nm-18nm) compared to CNF (32nm-44nm). Response surface methodology (RSM) study shows that the percentage of carbon yield is affected by the reaction temperature and the NG to N2 ratio. Using RSM, the maximum amount of 547.35% of carbon is predicted to produce using the operating reaction temperature of 895°C, reaction time at 1.95hours and NG:N2 ratio at 0.61.